Efforts to strengthen anatomic pathology diagnostic services for cancer in sub-Saharan Africa: a scoping review protocol - Katherine Van Loon; Elia John Mmbaga; Marcia Edelweiss; Dianna L. Ng; Asteria Herman Kimambo; Edda Vuhahula; Beatrice Paul Mushi; Omolade Adegoke; Johanna Goldberg; Pendo M. Ibrahim; Zainab Illonga; Julia Jackman; et al. (BMJ Open)
Introduction Sub-Saharan Africa bears a disproportionate burden of cancer-related morbidity and mortality compared with high-resource settings. Although pathology services are essential to providing optimal oncological care, diagnostic capacity in sub-Saharan Africa is insufficient for the cancer burden. This scoping review will be conducted to summarise the current state of practices and evidence for interventions and implementation strategies to improve anatomic pathology services for cancer in the region. The objective of this scoping review is to describe efforts to strengthen capacity for anatomic pathology services in sub-Saharan Africa. The information gathered will be used to inform the design of future pathology capacity-building interventions. The primary aim of the scoping review is to comprehensively map the existing evidence on initiatives aimed at enhancing the capacity for pathology services.Methods and analysis This study will follow Joanna Briggs Institute methodology for scoping reviews. MEDLINE, Embase, Cochrane Central and African Index Medicus will be searched for articles published in English and Portuguese with no limitations placed on date or publication type. A limited search for grey literature will be conducted using the WHO Institutional Repository for Information Sharing. Two independent reviewers will screen all articles, extract data and complete the descriptive analysis. All discrepancies will be resolved using a third reviewer. The results will be reported using the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR). This review will consider scientific literature from published primary studies as well as scoping and systematic reviews related to capacity-building efforts to strengthen anatomic pathology services in any sub-Saharan African country. All study designs will be considered, including quantitative, qualitative and/or mixed-methods studies.Ethics and dissemination Ethical approval is not required for this study. Dissemination of findings from this work will include the publication of the results in a peer-reviewed journal and presentations at conferences.Protocol registration number Open Science Framework, https://osf.io/6cmhg.